The effect of letrozole on liver function test in polycystic ovarian syndrome with subfertile patient with and without fatty liver disease - Sarkar, Binita; Akter, Fatema; Jikria, Najmatun; Sikdar, Koushik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Polycystic ovarian syndrome (PCOS) is a common endocrine disorder characterized by subfertility, insulin resistance and metabolic dysfunction, commonly associated with nonalcoholic fatty liver disease (NAFLD). Letrozole is a first line ovulation induction agent, superior to clomiphene citrate but liver effects in PCOS patients with and without fatty liver disease has not been sufficiently explored. This study aims to determine the effect of letrozole on liver function tests (LFTs) in subfertile PCOS patients stratified by the presence of fatty liver disease. Methods: This cross-sectional observational study carried out at department of obstetrics and gynecology, Shaheed Syed Nazrul Islam Medical College Hospital, Kishoreganj, Bangladesh from 1st October 2023 to 31st of March 2024. The study included 150 subfertile women with PCOS who had been divided equally between groups with or without fatty liver disease. The baseline characteristics, metabolic profiles and LFT parameters were analyzed. Results: Across both groups, letrozole improved ovulation and pregnancy rates, but the patients with fatty liver disease had markedly increased LFT parameters compared to those without, for example (ALT: 39±7.9 versus 25.5±6.4 U/l; p<0.001). Fatty liver group also had worse metabolic markers. In patients with fatty liver, 20% of patients developed adverse liver effects. Conclusions: Letrozole is effective for ovulation induction in subfertile PCOS patients but is hepatotoxic particularly if the patient has associated fatty liver disease. In high risk groups, therapists should closely monitor liver function.